Collaboration Between The State And Nii Crisis Center In Containing Religious Extremism And Terrorism In Indonesia - Hariyanto, Hariyanto; Zayyadi, Ahmad; Hariz, Hajar Salamah Salsabila (DE LEGA LATA: JURNAL ILMU HUKUM, 2025)
The article in front of the reader is the result of research related to the role of the State and the Indonesian Islamic State Crisis Center or abbreviated as the NII Crisis Center in efforts to overcome religious extremism and terrorism in Indonesia. Through religious moderation is also a good way in efforts to overcome religious radicalism and terrorism in Indonesia. The diversity of ethnicity, race, religion and culture is a characteristic of the heterogeneous Indonesian nation. This diversity is an integrating force to bind society in the framework of the united ummatan. However, lately the problem of radicalism and extremism in Indonesia is still rampant and even almost difficult to contain if not supported by a support system in efforts to overcome it, both in government circles or elements of society. As in the incident in the Garut area of West Java, there has been an oath of allegiance to dozens of children carried out by the radical NII group. Even after being investigated, there were as many as 59 teenagers who had been exposed to the radical ideology of the NII. The issue of religious extremist movements in Indonesia has begun to emerge again, such as the recruitment process of the Indonesian Islamic State (NII) organization carried out through religious studies under the pretext of religion, so that the role of the state and Islamic mass organizations is greatly needed. The method used in this article is to use the rule theory related to the role of the state and the NII Crisis Center in efforts to overcome radicalism, extremism, and terrorism in Indonesia